Coding the Self: The Infopolitics and Biopolitics of Genetic Sciences - Koopman, Colin (The Hastings Center report, 2020)
This essay compares three models for conceptualizing the political and ethical challenges of contemporary genetics, genomics, and postgenomics. The three analytical approaches are referred to as the state-politics model, the biopolitical model, and the infopolitical model. Each of these models is valuable for different purposes. In terms of their influence in contemporary discussions, the first is by far the dominant approach, the second is gaining in importance, and the third is almost entirely neglected. The widespread neglect of the infopolitical dimensions of genetic sciences that are the focus of the third model is puzzling in light of the fact that genetics, genomics, and postgenomics are all preeminent information sciences. The infopolitical model thus aims to bring into clearer view the specific political and ethical problems engendered by this informational nature of the genetic sciences. This model offers a way of understanding how ethically salient and politically fraught conceptual assumptions can be embedded in informational architectures such as algorithms and the formats (or data structures) upon which they rely.